Intergenerational and Intercultural Differences in Work Values in Quebec and the United Arab Emirates - Wils, Thierry; Saba, Tania; Waxin, Marie-France; Labelle, Christiane (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2011)
We examined the impact of generations on individual work values in Quebec and the United Arab Emirates. We used two convenience samples, encompassing 186 French-speaking Canadians in Quebec and 252 Arabs in the United Arab Emirates. We used an abridged version of Wils, Luncasu and Waxin (2007) work value inventory, including 28 work values arranged on four poles: self-enhancement, self-transcendence, openness-to-change and conservation. Using multidimensional analyses, we validated the structuring of our work value inventory in both samples. We used MANCOVA analyses to examine intergenerational and cultural work value differences. In the Quebec sample, there were no significant differences between generations in their scores on the four work value poles, supporting Inglehart’s theory (1971, 2008). In the Arab sample, the younger generation attached less importance to self-enhancement, but more importance to self-transcendence than the older generation with a small effect size. Inglehart’s theory (1971, 2008) also predicts a shift to post-materialistic values associated with the transition from a poorer to a richer society. We found that cultural origin had no significant, direct effect on the average score on each work value pole. Gerhart and Fang (2005) also found that the impact of culture is often exaggerated in HR management research. We found a significant interaction between cultural origin and gender for the self-transcendence pole. Since we found a high diversity in work values among generations, our results do not support the idea that human resource management practices should be adjusted for different generations. Our study confirms the importance of selective hiring within high performance work systems (HPWS), because within each country and each generation, there were respondents with a wide variety of work value preferences, making it possible to recruit selectively in order to achieve the best fit between the work values of employees and the philosophical principles underlying HPWS.